Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
Lười làm quá!
a) f ( 1/2 ) = 4 . ( 1/2 )2 - 7 = 4 . 1/4 - 7 = 1 - 7 = - 6
f ( 3 ) = 4 . 32 - 7 = 4 . 9 - 7 = 36 - 7 = 29
f 0 ) = 4 . 02 - 7 = 4 . 0 - 7 = 0 - 7 = - 7
f ( - 2 ) = 4 . ( - 2 )2 - 7 = 4 . 8 - 7 = 32 - 7 = 25
b) f ( x ) = 93
4 . x2 - 7 = 93
=> 4 . x2 = 93 + 7
=> 4 . x2 = 100
=> x2 = 100 : 4
=> x2 = 25
=> x2 = 52
=. x = 5 hoặc x = - 5
Vậy ...
a/ ta có: f(0)=9*02-2=-2
f(-1/3)=9*(-1/3)2-2=-1
f(\(3\sqrt{2}\)
\(a.\)
Theo đề , ta có : \(y=f\left(x\right)=4x^2-5\)
\(\Rightarrow\)
\(f\left(3\right)=4.\left(3\right)^2-5=31\)
\(f\left(-\frac{1}{2}\right)=4.\left(-\frac{1}{2}\right)^2-5=-4\)
\(b.\)
Ta có : \(f\left(x\right)=-1\)
\(\Rightarrow4x^2-5=-1\)
\(\Rightarrow4x^2=-1+5=4\)
\(\Rightarrow x^2=4:4=1\)
\(\Rightarrow x=\sqrt{1}=1\)
\(c.\)
Ta có :
\(f\left(x\right)=4x^2-5\)
\(\Rightarrow f\left(x\right)=4.\left(x\right)^2-5\) \(\left(1\right)\)
\(f\left(-x\right)=4.\left(-x\right)^2-5=4.\left(x\right)^2-5\) \(\left(2\right)\)
Từ \(\left(1\right)\) và \(\left(2\right)\Rightarrow f\left(x\right)=f\left(-x\right)\)
22410
+/ f(2) = -4.22 + 3
f(2) = - 13
+/ f(-3) = -4.(-3)2 + 3
f(-3) = - 33
+/ f(-2) = -4.( - 2 )2 + 3
f(-2) = - 13